2016
DOI: 10.5604/15093492.1198853
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Comprehensive Musculoskeletal Rehabilitation on Clinical Status of Ankylosing Spondylitis Patients

Abstract: Na ro do wy In sty tut Ge ria trii, Reu ma to lo gii i Re ha bi li ta cji im. prof. dr hab. med. Ele ono ry Re icher, Polska 2 Za kład Re ha bi li ta cji Od dzia łu Fi zjo te ra pii, II Wy dział Le kar ski, War szaw ski Uni wer sy tet Me dycz ny, Polska 3 Cen tral ny In sty tut Ochro ny Pra cy-Pań stwo wy In sty tut Ba daw czy, Polska 1 Prof. E. Re icher Na tio nal In sti tu te of Ge ria trics, Rheu ma to lo gy and Re ha bi li ta tion, Poland 2 Re ha bi li ta tion De part ment, Di vi sion of Phy sio the ra py,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Cluster 7 relates to the rehabilitation treatment of AS. Researchers have demonstrated that comprehensive rehabilitation is beneficial for improving the quality of life of AS patients (36). Therefore, an effective method for assessing patient status is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Cluster 7 relates to the rehabilitation treatment of AS. Researchers have demonstrated that comprehensive rehabilitation is beneficial for improving the quality of life of AS patients (36). Therefore, an effective method for assessing patient status is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…The search was limited to articles in the English language, starting from the earliest papers to May 2017 and carried out from the scientific search guidelines published in 2011. 12 Since there are already published reports in the literature for inflammatory rheumatic diseases, [13][14][15][16][17][18][19] we did not plan to address this issue in this article. Because the literature was scarce in AIDs, this overview contains general information and brief descriptions on some of the clinical entities of AIDs which are commonly encountered in the Physical and Rehabilitation Medicine (PRM) branch, particularly due to musculoskeletal involvement.…”
Section: Introductionmentioning
confidence: 99%